Tree-rings reflect the impact of climate change on Quercus ilex L. along a temperature gradient in Spain over the last 100years - Gea-Izquierdo, G.; Cherubini, P.; Cañellas, I. (Forest Ecology and Management, 2011)
We analyzed tree rings over the past 100 years to understand the response of Quercus ilex L. to climate change at four different sites along a temperature gradient in a highly anthropogenically transformed ecosystem. To test the hypothesis of a climate change related decrease in productivity at warmer sites, we discuss the effect of historical management on the growth of forest stands and the spatio-temporal variability of growth in response to climate, analyzing departures from linearity in that relationship. We reconstructed stand history and investigated past growth trends using tree-rings. Then we used a dendroecological approach to study the regional, local and age-dependent response to climate, analyzing the relationship between precipitation and tree growth using non-linear mixed models. Tree rings reﬂected the origin of the studied landscape, mainly a simpliﬁcation of an original closed forest and progressive canopy opening for agrosilvopastoral purposes after the mid 1800s. As expected, trees were principally responding to water availability, and regional growth (as expressed by the ﬁrst principal component from the matrix of chronologies) was highly responsive to hydrological year precipitation (r = 0.7). In this water limited ecosystem, the response of growth to precipitation was asymptotic and independent of age, but variable in time. Maximum growth was variable at the different sites and the non-linear function of growth saturated (i.e. reached an asymptote) at temperature dependent site speciﬁc precipitation levels within the range considered in the region to lead a shift towards deciduous species dominated woodlands (around 600 mm, variable with mean temperature). Only trees at warmer sites showed symptoms of growth decline, most likely explained by water stress increase in the last decades affecting the highly transformed open (i.e. low competition) tree structure. Stands at colder locations did not show any negative growth trend and may beneﬁt from the current increase in winter temperatures. Coinciding with the decrease in productivity, trees at warmer sites responded more to moisture availability, exhibited a slower response to precipitation and reached maximum growth at higher precipitation levels than trees at colder sites. This suggests that warmer stands are threatened by climate change. The non-linear response of growth to precipitation described is meaningful for different ecological applications and provides new insights in the way trees respond to climate.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: competition; Dendroecology; Drought; Non-linear response; water stress